Effectiveness of an Secondary Prevention Program in Chronic Kidney Disease (2013)
ABSTRACT: Background: There are many programs which focus on late-stage chronic kidney disease (CKD), and it is considered that further evidence needs to be generated regarding the effectiveness of the programs used before renal replacement therapy. Study Design: A cohort study. Settings & Participants: Patients over 15 years of age who had been diagnosed with CKD according to the KDOQI (Kidney Disease Outcomes Quality Initiative) guidelines and who had undergone conventional treatment (CT) or a renal protection program (RPP). These were patients of two Colombian health insurance companies. Predictors: Age, sex, marital status, comorbidities, CKD stage, and clinical indicators. Outcomes: First CKD progression, and need for renal replacement therapy (RRT). Measures: Clinical marker. Results: The RPP is structurally and functionally different from the CT. It offers the interdisciplinary management of patients, a greater number of medical appointments, and patients start to receive treatment at younger ages and at earlier stages of their condition. The clinical markers of the patients following the RPP are within adequate ranges, and their renal function is less impaired, despite the differences in basal conditions. Upon finishing the study, we found that patients who received CT had a higher risk of receiving nephrotoxic drugs and not receiving nephroprotective drugs. The explanatory variables for the first progression were age, stage, history of dyslipidemia, and hemoglobin, potassium, and albumin levels.These variables, together with glycemia levels were also valid for RRT, except for history of dyslipidemia, as it was not significant. Upon adjusting for the explanatory variables, it was found that belonging to the RPP and attending more appointments had a protective effect in the process of controlling renal damage. Limitations: A possible selection bias. Conclusions: Belonging to a structured renal protection program is an effective way to keeping the clinical markers associated with renal impairment within normal ranges.